Non-Invasive Adaptation Service for Web-based Content Management Systems - CONLAN, OWEN; WADE, VINCENT; KOIDL, KEVIN (My University, 2009)
Most Adaptive Hypermedia Systems today focus on providing an adaptive portal or presentation/application through which adaptive retrieved content is delivered. Moreover the content used by such adaptive systems tends to be handcrafted for adaptivity, i.e. from closed corpus repositories. If adaptive hypermedia is to become more mainstream we need the ability to embed adaptive information retrieval and composition techniques within existing Web-based Content Management Systems (WCMS) e.g. Wiki, Drupal. However the effort and expense in fundamentally re-engineering such WCMS or developing completely new adaptive WCMS, is very high. This research explores the architectural and technical issues involved in providing a third party adaptive service which is more easily plugged into existing WCMS. The advantage of this approach is that it doesn?t break the current browsing paradigm of freely navigating across different independent web sites on the web. In order to address this challenge we introduce a third party Adaptive Service that enables a unified cross-website personalized experience by discretely interfacing with separate independent WCMS. Thus the Adaptive Service strives to personalize the users experience when accessing each WCMS in a non-invasive manner by not adversely interfering with the web sites overall look and feel, content and functionality without losing the web sites identity and fundamental experience. This paper describes the design and an initial use case supported implementation example of this Adaptive Service. It also provides a survey that assesses the feasibility of the services integration with leading WCMS.
Proceedings of the First International Workshop on Dynamic and Adaptive Hypertext: Generic Frameworks, Approaches and Techniques (DAH2009)
First International Workshop on Dynamic and Adaptive Hypertext: Generic Frameworks, Approaches and Techniques (DAH2009)
PUBLISHED
Torino, Italy
Keywords: Open Corpus; Adaptive Hypermedia; Web-based Content Management Systems (WCMS); Adaptive Hypermedia Strategies; Intelligent Content & Communications